Resilience, post-traumatic growth, and work engagement among health care professionals after the Great East Japan Earthquake: A 4-year prospective follow-up study - Nishi, Daisuke (J Occup Health, 2016)
OBJECTIVES: Although attention has been paid to post-traumatic stress disorder (PTSD) among health care professionals after disasters, the impact of traumatic events on their work has not been elucidated. The aim of this study was to examine whether disaster-related distress, resilience, and post-traumatic growth (PTG) affect work engagement among health care professionals who had been deployed to the areas affected by the Great East Japan Earthquake that occurred on March 11, 2011. METHODS: We recruited disaster medical assistance team members who were engaged in rescue activities after the earthquake. The short version of the Resilience Scale (RS-14) and Peritraumatic Distress Inventory (PDI) were administered one month after the earthquake, and the short form of Posttraumatic Growth Inventory (SF-PTGI) and Utrecht Work Engagement Scale (UWES) were administered four years after the earthquake. Work engagement is composed of vigor, dedication, and absorption. Regression analyses were used to examine the relationship of UWES with RS-14, PDI, and SF-PTGI. RESULTS: We obtained baseline data of 254 participants in April 2011, and 191 (75.2%) completed the follow-up assessment between December 2014 and March 2015. The results showed that RS-14 predicted vigor, dedication, and absorption; in addition, SF-PTGI was positively related with these three parameters (p<0.01 for all). CONCLUSIONS: Resilience at baseline and PTG after rescue activities may increase work engagement among health care professionals after disasters. These findings could be useful for establishing a support system after rescue activities during a large-scale disaster and for managing work-related stress among health care professionals.